Robert Seymour and nineteenth-century print culture : sketches by Seymour and comic illustration - Maidment, Brian (Routledge studies in nineteenth century literature, 2021)
"Robert Seymour and Nineteenth Century Print Culture is the first book length study of the original illustrator of Dickens's Pickwick Papers. Discussion of the range and importance of Seymour's work as a jobbing illustrator in the 1820s and 1830s is at the centre of the book. A bibliographical study of his prolific output of illustrations in many different print genres is combined with a wide-ranging account of his major publications. Seymour's extended work for The Comic Magazine, New Readings of Old Authors and Humorous Sketches, all described in detail, are of particular importance in locating the dialogue between image and text at the moment when the Victorian illustrated novel is coming into being"--